Experiments on the rotational capacity of beams made of high‐strength steel. Issue 1 (8th February 2018) - Schillo, Nicole; Feldmann, Markus
Abstract: The rotational capacity of beams made of high‐strength steel grades S700 and S960 was investigated within the scope of the RUOSTE research project, which was partly funded by the RFCS. Beams made of high‐strength steel are supposed to have a lower rotational capacity, and are thus excluded from plastic/plastic design according to [1], [2]. Although the strain hardening of high‐strength steel material is generally lower than that of mild steels, for some structures with discrete plastic hinges, the rotational capacity might be still sufficient to reach the respective cross‐section classification. In the research presented here, eight tests on beams in bending were carried out to assess the limit of cross‐section class 1 for high‐strength steel.